Durum wheat diversity for heat stress tolerance during inflorescence emergence is correlated to TdHSP101C expression in early developmental stages - Bento, Miguel; Pereira, Sónia Gomes; Viegas, Wanda; Silva, Manuela (PLOS ONE, 2017)
The predicted world population increase along with climate changes threatens sustainable agricultural supply in the coming decades. It is therefore vital to understand crops diversity associated to abiotic stress response. Heat stress is considered one of the major constrains on crops productivity thus it is essential to develop new approaches for a precocious and rigorous evaluation of varietal diversity regarding heat tolerance. Plant cell membrane thermostability (CMS) is a widely used method for wheat thermotolerance assessment although its limitations require complementary solutions. In this work we used CMS assay and explored TdHSP101C genes as an additional tool for durum wheat screening. Genomic and transcriptomic analyses of TdHSP101C genes were performed in varieties with contrasting CMS results and further correlated with heat stress tolerance during fertilization and seed development. Although the durum wheat varieties studied presented a very high homology on TdHSP101C genes (>99%) the transcriptomic assessment allowed the discrimination between varieties with good CMS results and its correlation with differential impacts of heat treatment during inflorescence emergence and seed development on grain yield. The evidences here reported indicate that TdHSP101C transcription levels induced by heat stress in fully expanded leaves may be a promising complementary screening tool to discriminate between durum wheat varieties identified as thermotolerant through CMS.